Cyclization of 5-hexynoic acid to 3-alkoxy-2-cyclohexenones - Hylden, Anne T.; Uzelac, Eric J.; Ostojic, Zeljko; Wu, Ting-Ting; Sacry, Keely L.; Sacry, Krista L.; Xi, Lin; Jones, T. Nicholas (Beilstein Journal of Organic Chemistry, 2011)
The one-pot cyclization of 5-hexynoic acid to produce 3-alkoxy-2-cyclohexenones proceeds in good yields (58–90%). 3-Hexynoic acid was converted to its acyl chloride with the aid of oxalyl chloride and was cyclized to 3-chloro-2-cyclohexenone upon addition of indium(III) chloride. Subsequent addition of alcohol nucleophiles led to the desired 3-alkoxy-2-cyclohexenones.
Keywords: acyl chlorides; alcohols; alkynes; cyclization; Lewis acids